Examining Private Universities' Blue Ocean Leadership - Edi Sumarya; Brigida Endah Nuraeni (UNIVED Press, 2025)
Blue Ocean Leadership (BOL) is a strategic leadership approach that focuses on creating new market space, redefining the boundaries of competition, and optimizing resources to achieve sustainable competitive advantage. Although it has been widely applied in the business sector, empirical studies on BOL in the context of higher education, especially in Indonesian Private Universities (PTS), are still limited. This research aims to explore the implementation of BOL in XYZ University Batam, a large private university that is facing intense competitive pressures and demands for organizational transformation. Using a qualitative case study approach, the research relies on in-depth interviews with university leaders, lecturers, and education staff, as well as a review of the institution's strategic documents. The findings show that the implementation of BOL contributes to driving organizational innovation, improving the efficiency of internal processes, and generating a distinctive value proposition that differentiates the university from its competitors. However, there are a number of challenges in implementation, including organizational cultural resistance, limited resource capacity, and low technical understanding of the operational principles of BOL. This research makes a theoretical contribution to the strengthening of strategic leadership studies in the higher education sector and provides practical recommendations for PTS in adopting more responsive, adaptive and innovative leadership strategies to strengthen the institution's competitive position amid increasingly complex global dynamics.